Implications of Shariah financial technology in increasing financial inclusion to Micro, Small, and Medium Enterprises - Yuneline, Mirza Hedismarlina (Penerbit Universiti Kebangsaan Malaysia, 2022)
Micro, Small, and Medium Enterprises (MSMEs) have long been understood as playing a significant role in the economic development of a country. However, MSMEs have not been able to make a significant contribution to the economy due to constraints of capital problems and limitations in meeting the requirements of bureaucracy and banking administration when applying for loan funds from banks. Due to the limited services provided by banks, the emergence of financial technology (fintech) innovation is an opportunity for MSMEs to overcome their capital problems. However, the use of fintech triggers risks borne by users or consumers such as cyber risks related to data security, data ownership, privacy, and data governance. Shariah-based fintech is one solution to extend financial inclusion to MSMEs to overcome their capital problems. The purpose of this research is to analyze the development and the contribution of Shariah fintech in strengthening the financial inclusion of MSMEs. The method used in this qualitative descriptive research is by describing and interpreting the observations and findings of 5 Shariah fintech platforms that focus on MSMEs’ funding as the research sample. The result shows that the market share of Shariah fintech is 2.01% of the total fintech platform and it is caused by the lack of Shariah financial literacy. In terms of risk, even though the financing risk is relatively lower than Bank’s Non-Performing Loan, other risks may arise, such as cyber risk and Shariah compliance risk. In order to mitigate the risks, the authority needs regulations for cyber security for consumer protection and supervision of Shariah compliance by the National Shariah Council of the Indonesian Ulama Council.